Neuronal Ceroid Lipofuscinosis in Border Collie Dogs in Japan: Clinical and Molecular Epidemiological Study (2000–2011) - Keijiro Mizukami; Takuji Kawamichi; Hiroshi Koie; Shinji Tamura; Satoru Matsunaga; Shigeki Imamoto; Miyoko Saito; Daisuke Hasegawa; Naoaki Matsuki; Satoshi Tamahara; Shigenobu Sato; Akira Yabuki; et al. (The Scientific World Journal)
Neuronal ceroid lipofuscinosis (NCL) is an inherited, neurodegenerative lysosomal disease that causes premature death. The present study describes the clinical and molecular epidemiologic findings of NCL in Border Collies in Japan for 12 years, between 2000 and 2011. The number of affected dogs was surveyed, and their clinical characteristics were analyzed. In 4 kennels with affected dogs, the dogs were genotyped. The genetic relationships of all affected dogs and carriers identified were analyzed. The survey revealed 27 affected dogs, but there was a decreasing trend at the end of the study period. The clinical characteristics of these affected dogs were updated in detail. The genotyping survey demonstrated a high mutant allele frequency in examined kennels (34.8%). The pedigree analysis demonstrated that all affected dogs and carriers in Japan are related to some presumptive carriers imported from Oceania and having a common ancestor. The current high prevalence in Japan might be due to an overuse of these carriers by breeders without any knowledge of the disease. For NCL control and prevention, it is necessary to examine all breeding dogs, especially in kennels with a high prevalence. Such endeavors will reduce NCL prevalence and may already be contributing to the recent decreasing trend in Japan.